Acceptance and Utilization of Long-Lasting Insecticide-Treated Nets (LLINs) by the Community of Mamboro Sub-district and Katiku Tana Sub-district, Central Sumba Regency, East Nusa Tenggara - Irfan, Irfan; Landi, Soleman; Ora, Anderias Parawatu; Patmawati, Try Ayu; Kambuno, Norma Tiku (Global Medical & Health Communication (GMHC), 2023)
Distribution of mosquito nets is one healthcare strategy implemented to control the number of malaria cases in Indonesia. East Nusa Tenggara is one of the provinces contributing to high malaria rates. Cases are high in several areas, including Central Sumba regency. This study aimed to describe the behavior of the people of Mamboro and Katiku Tana sub-districts in using long-lasting insecticide-treated nets (LLINs), the number of LLINs owned, number of beds, number of family members, number of pregnant women and toddlers, distribution of LLINs in families, and LLINs utilization. This is a descriptive quantitative study with a cross-sectional design. The research was conducted in the work area of the Mananga Health Center of Susu Wendewa village of Mamboro sub-district and Malinjak Health Center of Makata Keri village of Katiku Tana sub-district, Central Sumba regency. The research was carried out from 9–19 September 2021 with 341 heads of families as respondents. Data were collected using questionnaires and in-depth interviews. Most families had LLINs (n=287; 94.1%); the total number of LLINs owned was 341, used by 1,220 (94.7%) family members with ten pregnant women and 35 children under five. The number of installed LLINs was 290 units (85%), LLINs obtained from the health centers within 1–3 months was 44% (126 families), 314 units (92%) were used while sleeping, and there were still family members who did not use LLINs every night. We conclude that the acceptance and utilization of LLINs should not stop at the distribution of LLINs to the public and must be supported by an evaluation in the form of regular surveys to ensure that LLINs are correctly used.